Interaction between diazotrophic bacteria and N-fertilizer doses on sugarcane crop - Oliver, Rodrigo [UNESP]; de Almeida Silva, Marcelo [UNESP] (Taylor & Francis, 2018)
The current study aimed to verify the effect of the inoculant constituted by diazotrophic bacteria applied in different ways, associated to different nitrogen (N)-fertilizer doses, on the yield and N utilization efficiency of sugarcane ratoon. The use of inoculant did not affect the N content in leaves, the chlorophyll content, tiller number, stalk diameter, or any of the other assessed technological attributes. However, the use of inoculant associated to doses of 60 and 90 kg N ha−1 promoted increase in stalk yield, dry matter, and N accumulation and efficiency of N fertilizer, and, on the other hand, the association of inoculant with 120 kg N ha−1 caused reduction of these parameters.
Keywords: biological nitrogen fixation; inoculant; nitrogen; Saccharumspp